The Influence of Social Media Marketing, Country of Origin, and Product Features on Purchase Intention of Xiaomi Smartphones for Generation Z in Surabaya - Aldo Nugraha Adeyawarman; Hery Pudjoprastyono; Nurkholish Majid (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
There has been tremendous growth in information and communication technology infrastructure in Indonesia. Along with this, the demand for various media and communication devices has also increased, considering the needs of the community for diverse communication tools. This condition also encourages increasingly tight competition in the telecommunications industry. In connection with the tight competition in the telecommunications industry, it is important to examine what influences purchasing intention. This study aims to determine the influence and analyze the Influence of Social Media Marketing, Country of Origin, and Product Features on Purchase Intention of Xiaomi Smartphones for Generation Z in Surabaya. This research method is quantitative with a purposive sampling technique. The sample consists of 160 respondents, consisting of Generation Z in Surabaya and those interested in Xiaomi smartphones. Data analysis was carried out using the Partial Least Squares (PLS) method with the help of SmartPLS 3. The results of this study are 1) Social media marketing has a positive and significant effect on the purchase intention of Xiaomi smartphones for Generation Z in Surabaya. 2) Country of origin has a positive and significant effect on the purchase intention of Xiaomi smartphones for Generation Z in Surabaya. 3) Product features have a positive and significant effect on the purchase intention of Xiaomi smartphones for Generation Z in Surabaya.